Kepribadian Big Five Sebagai Prediktor Perilaku Vandalisme pada Siswa SMAN 02 Batu - Agil Prayogo; Tutut Chusniyah; Farah Tantiani (Universitas Negeri Malang, 2021)
Vandalism is an act of destroying goods, facilities, or environmental arrangements that are carried out intentionally without the owner's permission and is a form of aggression. The act of aggression is caused by several factors, one of which is the personality of the individual. This study aims to: (1) Know the level of the big five personality traits (2) Knowing the level of vandalism (3) big five personality is a predictor of vandalism behavior in students. This study uses a quantitative approach with a descriptive causality design. The sample of this study amounted to 90 people. The sampling technique used was purposive sampling with the characteristics of being students of class XI Science, Social Sciences, and Language at SMAN 02 Batu. The instruments used are in the form of a scale of vandalism and short scale and extra-shorts forms of big five inventory. Analysis of the data used is descriptive analysis techniques and simple regression analysis used to determine whether the big five personality is a predictor of vandalism behavior in students. The results of the analysis obtained several conclusions as follows: (1) generally the level of vandalism in class XI students of SMAN 02 Batu is in the high category; (2) extraversion, conscientiousness, and neuroticism traits in SMAN 02 Batu students are generally in the low category, while trait agreeableness and openness are generally in the high category. (3) extraversion trait is a predictor of vandalism behavior in students of SMAN 02 Batu, (R equal 0.382 R square 0.088 sig. 0.004 less than 0.05). The results of this study are suggested that the schools make prevention efforts such as deflecting offenders to change destructive behavior into activities that have positive values. For further research, it is expected to be able to examine more in the aspects that exist in each variable, as well as the factors that influence the two variables. Vandalisme adalah suatu tindak yang dilakukan dengan sengaja merusak lingkungan dan merupakan bentuk dari agresi. Ada beberapa faktor yang menyebabkan tindakan tersebut, salah satunya kepribadian dari individu. Penelitian ini bertujuan: (1) Mengetahui tingkat trait kepribadian big five (2) Mengetahui tingkat vandalisme (3) big five merupakan aspek prediksi perilaku vandalisme pada siswa. Dalam penelitian ini digunakan pendekatan kuantitatif deskriptif kausalitas. Sampel penelitian ini berjumlah 90 orang. Teknik sampling yang digunakan adalah purposive sampling dengan karakteristik yaitu merupakan siswa kelas XI IPA, IPS, dan Bahasa di SMAN 02 Batu. Istrumen yang digunakan berupa skala vandalisme dan skala short and extra-shorts forms of big five inventory. Analisis data yang digunakan adalah teknik analisis deskriptif dan analisis regresi sederhana yang digunakan untuk mengetahui apakah kepribadian big five sebagai prediktor perilaku vandalisme pada siswa. Hasil analisis diperoleh beberapa kesimpulan sebagai berikut: (1) umumnya tingkat vandalisme pada siswa kelas XI SMAN 02 Batu berada pada kategori tinggi; (2) trait extraversion, conscientiousness, dan neuroticism pada siswa SMAN 02 Batu secara umum pada kategori rendah, sementara trait agreeableness dan openness secara umum pada kategori tinggi. (3) trait extraversion merupakan prediktor perilaku vandalisme pada siswa SMAN 02 Batu, (R sama dengan 0,382 R square 0,088 sig. 0,004 kurang dari 0,05). Hasil penelitian ini disarankan agar pihak sekolah melakukan upaya pencegahan seperti, deflecting offenders guna mengubah perilaku perusakan menjadi kegiatan yang memiliki nilai positif. Bagi penelitian selanjutnya diharapkan untuk dapat mengkaji lebih dalam aspek-aspek yang ada pada masing-masing variabel, serta faktor-faktor yang mempengaruhi dari kedua variabel